(untitled) (Bangladesh Journal of Urology, 2020)
Objective: To evaluate and compare the outcome of buccal mucosal graft urethroplasty of unilateral and circumferential urethral mobilization for the management of bulbar urethral stricture. Methods: Seventy patients having bulbar urethral strictures admitted in the Department of Urology, Dhaka Medical College Hospital, Dhaka between January 2010 to December 2011. Patients were divided into two groups. Group-I, underwent unilateral urethral mobilization, and Group-II, underwent circumferential urethral mobilization for buccal mucosa graft urethroplasty. All patients were followed up at least six months. The statistics used to analyze the data were descriptive statistics, and p value <0.05 was considered as significant. Results: Mean±SD of age in Group-II and Group-I were 41.1±9.2 and 37.4±8.2 years respectively. All the baseline findings were identically distributed between the groups. Comparison of outcome at month 3 showed that peak urinary flow rate increased from their baseline figures, but the increase was significantly more in the unilateral group than that in the circumferential group (21.2±1.2 vs. 18.9±2.0 Qmax, p =< 0.001). After 6 months, evaluation showed that the peak urinary flow rate significantly higher in Group-I, than that in Group-II, (24.2±2.9 vs. 21.9 ± 3.3, p < 0.001). The voided urine volume was also significantly higher in Group-I, than that in Group-II (330.8±50.1 vs. 294.5±46.1 ml, p = 0.004). Consequently, PVR was lower in the former group than that in the latter group (11.6±3.3 vs. 14.1±2.9 ml, p = 0.002). Complications in unilateral urethral mobilization had a significantly lower (20%) than that of circumferential urethral mobilization(45.71%) (p=0.024). Conclusion: Buccal mucosa grafting is a versatile and effective treatment for the anterior urethral stricture, and the outcome is excellent following unilateral urethral mobilization in experienced hands. Bangladesh Journal of Urology, Vol. 19, No. 1, Jan 2016 p.32-37